Multifaceted Applications of Chitosan-Coated Zinc Oxide Nanoparticles: Implications for Antibacterial, Antifungal and Anticancer Activity - Kavitha, R.; Vanitha, N. (Asian Journal of Chemistry, 2025)
This study explores the anticancer and antimicrobial effects of zinc oxide nanoparticles (ZnO-NPs) synthesized from chitosan (CS) extracted from crab shells. In this green synthesis approach, chitosan acted as both a reducing and coating agent, resulting in the formation of stable CS-ZnO-NPs. The synthesized CS-ZnO-NPs were characterized by UV-Vis, FTIR, XRD, SEM, TEM and EDX analysis. The UV-Vis analysis indicated a strong absorption peak around 316 nm, confirming the successful synthesis of nanoparticles. The structural analysis conducted through XRD and microscopy showed that the nanoparticles were spherical and hexagonal shapes to cubic, with diameters between 60 and 150 nm. EDX spectra confirmed the elemental composition and fabrication of CS-ZnO-NPs. The biological evaluations showed CS-ZnO-NPs exhibited significant antibacterial and antibiofilm properties against Escherichia coli, Klebsiella pneumoniae and Staphylococcus aureus, along with antifungal effects against Aspergillus niger, Aspergillus flavus and Candida albicans. The anticancer activity of CS-ZnO-NPs was evaluated using the MCF-7 breast cancer cell line. Cytotoxicity assays showed dose- and time-dependent cell death with an IC50 of 10 µg/mL. Apoptotic features, such as reduction in cell size and fragmentation of the nucleus, were identified using AO/EB and DAPI staining. Besides that, green synthesized CS-ZnO NPs significantly inhibited migration of MCF-7 cells. The results indicate that chitosan-coated ZnO-NPs demonstrate significant antimicrobial and anticancer properties, positioning them as promising candidates for future biomedical applications.